ORTHOPAEDIC MANAGEMENT OF CHILDREN WITH OSTEOGENESIS IMPERFECTA. (Experience of Republican children’s orthopaedic center) (World Bulletin of Public Health, 2023)
Limitation of movement and fear from multiple fractures in children with Osteogenesis Imperfecta (OI) lead to decrease of comfort in normal daily life. Correction of deformation and proper medical treatment facilitates to achieve better functional results. In this paper, we present sixty-four patients with clinically diagnosed OI had been treated in Republican children’s orthopaedic center. There were 42 male and 22 female OI affected patients. Diagnosis was made according to clinical presentation and radiographic examination. 41 patients treated with intravenous third generation bisphosphonates – Zometa, every 4-6 months. 36 operations were done in 25 patients with lower limb deformation as described Sofield and Millar. All operations were performed in purpose of lower limb bone deformity correction. Fixation of lower leg bones after correction of deformation made by using different intramedullary nails and pins. Fassier Duval (FD) telescopic nail used in 19 patients (femur - 11, tibias - 13). In 3 patients with older age (15, 16 and 18 years old) fixation was made by Slim nails (femora – 3, tibia - 5). Ilizarov pins were used to fixate 4 tibias in 3 patients, due to difficulty of using FD nail.